Smoking and reverse causation create an obesity paradox in cardiovascular disease - Stokes, Andrew; Preston, Samuel H. (Obesity (Silver Spring, Md.), 2015)
Objective Many studies find that excess weight is associated with better survival among individuals with cardiovascular disease (CVD). Investigations were carried out to see whether this “obesity paradox” can be explained by biases. Methods The association between weight status and mortality in the US population ages 35 and above with CVD was investigated. Data were obtained from the National Health and Nutrition Examination Survey, 1988‐2010, linked to mortality records through 2011. To minimize biases resulting from illness‐induced weight loss, a reference category consisting of individuals who have always maintained normal weight was used. Age‐standardized mortality rates and Cox models were estimated, comparing overweight/obesity (body mass index (BMI) ≥25.0 kg m−2) to normal weight (BMI 18.5‐24.9 kg m−2). Results The paradox was present among those with overweight/obesity at the time of survey (hazard ratio (HR) = 0.89; 95% confidence interval (CI) 0.78‐1.01). However, when the reference category was limited to the always‐normal‐weight, the paradox disappeared (HR = 1.16; 95% CI 0.95‐1.41). When analysis was additionally confined to never‐smokers, mortality risks were significantly higher in the overweight/obesity group (HR = 1.51; 95% CI 1.07‐2.15; P = 0.021). Conclusions The findings provide support for the hypothesis that lower mortality among individuals with CVD and overweight/obesity is a product of biases involving reverse causation and confounding by smoking.